LEGAL REVIEW OF JUSTICE IN OCCUPATIONAL SAFETY AND HEALTH PROTECTION - Agoes Djatmiko; Elisabeth Pudyastiwi (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2024)
This study aims to determine how the implementing legal provisions and utilization of forest land conversion into plantations are oriented towards capitalism. This study uses a normative legal research method with the types of approaches, namely the legislative approach and the conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials, obtained by conducting a literature study. The results of the study indicate that Occupational Safety and Health (OHS) is an integral part of the protection of workers' rights, aims to create a safe and healthy work environment, and prevent work accidents and occupational diseases. In the Indonesian context, OHS is regulated through various legal instruments such as Law Number 1 of 1970 concerning Occupational Safety, Law Number 13 of 2003 concerning Manpower, and other derivative regulations that explain the standards and guidelines for the implementation of OHS. In addition, Indonesia has also ratified a number of international conventions from the International Labor Organization (ILO) which emphasize the importance of OHS protection for every worker. However, in its implementation, OHS regulations in Indonesia still face various challenges that lead to injustice in the protection of workers. Workers in the formal sector, especially those working in large companies, tend to get better OSH protection because the companies have sufficient resources to comply with existing regulations. In contrast, workers in the informal sector and small and medium enterprises (SMEs) often face more vulnerable situations, where OSH protection is minimal or even non-existent.